Análisis de contenido de la representación del cuerpo en un libro de texto de Educación Preescolar (2012)
Bodies are naturally and socially constructed. The social construction of the body influences the perception of self and others. Textbooks transmit a society’s cultural capital to its youngest citizens. The aim of the study was to describe how the body is portrayed in images featured in a Preschool textbook for the first grade of early childhood education. A content analysis of the images was performed using a coding frame based on previous studies. Girls and boys appeared nearly twice than adolescents, adults and older people. There was an equal representation of women and men regardless of age. It was found noticeable representation of a whole body dressed with street clothing. The activity level was predominantly static and in more than half of the images was not possible to distinguish the space where the bodies were located. The textbook as a conventional curricular material should be analyzed in terms of the hidden curriculum in order to provide alternative forms of understanding the body as a social and cultural construction. The results suggest the need for further analysis of the textbooks in early childhood education system.